Correlation of hyperpolarized 13C‐MRI data with tissue extract measurements. (4th March 2020) - Lee, Casey Y.; Lau, Justin Y. C.; Geraghty, Benjamin J.; Chen, Albert P.; Gu, Yi‐Ping; Cunningham, Charles H.
Abstract : Hyperpolarized (HP) 13 C MRI provides the means to monitor lactate metabolism noninvasively in tumours. Since 13 C ‐lactate signal levels obtained from HP 13 C imaging depend on multiple factors, such as the rate of 13 C substrate delivery via the vasculature, the expression level of monocarboxylate transporters (MCTs) and lactate dehydrogenase (LDH), and the local lactate pool size, the interpretation of HP 13 C metabolic images remains challenging. In this study, ex vivo tissue extract measurements (i.e., NMR isotopomer analysis, western blot analysis) derived from an MDA‐MB‐231 xenograft model in nude rats were used to test for correlations between the in vivo 13 C data and the ex vivo measures. The lactate‐to‐pyruvate ratio from HP 13 C MRI was strongly correlated with [1‐ 13 C ]lactate concentration measured from the extracts using NMR ( R = 0.69, p < 0.05), as well as negatively correlated with tumour wet weight ( R = − 0.60, p < 0.05). In this tumour model, both MCT1 and MCT4 expressions were positively correlated with wet weight ( ρ = 0.78 and 0.93, respectively, p < 0.01). Lactate pool size and the lactate‐to‐pyruvate ratio were not significantly correlated. Abstract : Ex vivo tissue extract measurements are used to correlate components of lactate metabolism (e.g. 13 C substrate delivery, the expression levels of monocarboxylate transporters and lactate dehydrogenases, and tumoural lactate concentration) to the observed in vivo 13 C data in MDA‐MB‐231 xenograft model in rats. Strong correlation was found between lactate‐to‐pyruvate ratio from hyperpolarized 13 C MRI and [1‐ 13 C ] lactate concentration measured with NMR.